MENGEMBALIKAN SUPREMASI ILMU PENGETAHUAN DUNIA ISLAM - Rofiq, Ahmad Choirul (IAIN Ponorogo, 2013)
Â A long time ago Muslim people used to achieve their golden ages for many centuries. The glory of civilization was accomplished in every aspect of life. That achievement was obtained because the leaders of Muslim society at that time were very responsible for their people and religion. They optimally created a large number of good environments and encouraged their people to do intellectual activities. Muslim people did not only gain their golden ages but also gave a significant contribution to the West so that the western people could carry out their renaissance and move themselves from the dark ages. Their awakening was attained well after they were successful to transfer knowledge from Muslim world to the west through intensive translation activities during Islamic government in Spain and Sicillia, as well as the crusades periode. Therefore, the Muslim people must revitalize their serious ijtihad activities continually to regain their intellectual supremacy and lead the world civilization again.Â ÙØµÙØª Ø§ÙØ£Ù Ø© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© â ÙÙ Ø§Ù ØªØ¯Ø§Ø¯ ØªØ§Ø±ÙØ®ÙØ§ Ø§ÙØ·ÙÙÙØ© â Ø¥ÙÙ Ø§ÙØ¹ØµØ± Ø§ÙØ°ÙØ¨Ù ÙÙ Ù Ø¬Ø§ÙØ§Øª Ø§ÙØÙØ§Ø©. ÙØØµÙÙØ§ Ø¹ÙÙ Ø§ÙØ¹Ø²Ø© ÙØ£Ù ÙÙØ§Ø© Ø§ÙØ£Ù ÙØ± ØÙÙ Ø°Ø§Ù Ù Ø¦ØªÙ ÙÙÙ ÙÙØ¹ÙØ§ Ø¨Ø§ÙÙ Ø³Ø¦ÙÙÙØ©. ÙØ§ÙØªÙ Ø§ÙÙÙØ§Ø© Ø¨Ø£Ù ÙØ± Ø§ÙØ£Ù Ø© ÙÙ Ø´Ø§ÙÙÙØ§ ÙØ¨Ø¯ÙÙÙÙ . ÙÙÙÙÙ ÙØ¤ÙØ§Ø¡ Ø§ÙÙÙØ§Ø© Ø¬ÙÙØ§ Ù ÙØ§Ø³Ø¨Ø§ ÙÙØ£ÙØ´Ø·Ø© Ø§ÙØ¹ÙÙ ÙØ©Ø Ø¨Ù Ø£Ø³ÙÙ Ø§ÙÙ Ø³ÙÙ ÙÙ ÙØ¨ÙØ±Ø§ ÙÙØºØ±Ø¨ ØØªÙ ÙØ¯Ø±ÙØ§ Ø¹ÙÙ